2008
DOI: 10.1073/pnas.0802025105
|View full text |Cite
|
Sign up to set email alerts
|

Methionine oxidation impairs reverse cholesterol transport by apolipoprotein A-I

Abstract: atherosclerosis ͉ dysfunctional HDL ͉ hypochlorous acid ͉ inflammation ͉ methionine sulfoxide reductase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
173
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(178 citation statements)
references
References 56 publications
1
173
1
3
Order By: Relevance
“…Oxidation of apoA-I by MPO impairs its ability to activate ABCA1 and LCAT, key steps in reverse cholesterol transport and HDL maturation (64,65,87). We found that MPO-mediated oxidation also severely limited the ability of apoA-I to exchange between the HDL-associated and lipid-free/lipidpoor states.…”
Section: Discussionmentioning
confidence: 73%
“…Oxidation of apoA-I by MPO impairs its ability to activate ABCA1 and LCAT, key steps in reverse cholesterol transport and HDL maturation (64,65,87). We found that MPO-mediated oxidation also severely limited the ability of apoA-I to exchange between the HDL-associated and lipid-free/lipidpoor states.…”
Section: Discussionmentioning
confidence: 73%
“…Zheng et al (15,16) first discovered that MPO, a leukocytederived heme protein implicated in atherosclerosis, binds to HDL via a specific binding domain on apoA1, promoting selective targeting of the lipoprotein in human plasma and atherosclerotic plaque for oxidative modification and a resultant loss of cholesterol efflux function. Independent studies have confirmed these observations (17,18) as well as shown that sitespecific oxidative modification of apoA1 within nascent HDL may inhibit the ability of the particle to activate LCAT, a critical process in HDL particle maturation and presumably the overall RCT pathway (19,20).…”
Section: High Density Lipoprotein (Hdl)mentioning
confidence: 81%
“…Oxidative modification of Met-148 or nitration of Tyr-166 by MPO in apoA-I was also associated with a loss of apoA-I-mediated activation of lecithin:cholesterol acyltransferase (LCAT), 130,133,136 which is crucial to help maintain a concentration gradient for cholesterol efflux from the cell to the HDL particle surface. The injection of purified MPO into mice reduced the net movement of labeled-cholesterol from macrophages to plasma and feces.…”
Section: Myeloperoxidase-mediated Protein Modificationsmentioning
confidence: 99%